Friendship [videorecording (Blu-Ray)] - DeYoung, Andrew (Director); Robinson, Tim, 1981-; Mara, Kate, 1983-; Grazer, Jack Dylan, 2003-; Rudd, Paul; Rydzewski, Andy; Karmin, Chloe; DeWitt, Keegan, 1982- (A24, 2025)
"Suburban dad Craig's anodyne existence is jolted to life when he falls hard for his charismatic new neighbor. But as their easy rapport gradually buckles under Craig's enthusiasm, his attempts to make a new adult companion threaten to ruin both of their lives."--